2013
DOI: 10.1038/ncomms3801
|View full text |Cite
|
Sign up to set email alerts
|

All-optical control and visualization of ultrafast two-dimensional atomic motions in a single crystal of bismuth

Abstract: In a bulk solid, optical control of atomic motion provides a better understanding of its physical properties and functionalities. Such studies would benefit from active control and visualization of atomic motions in arbitrary directions, yet, so far, mostly only one-dimensional control has been shown. Here we demonstrate a novel method to optically control and visualize two-dimensional atomic motions in a bulk solid. We use a femtosecond laser pulse to coherently superpose two orthogonal atomic motions in crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 41 publications
0
48
0
Order By: Relevance
“…Remarkably, due to the low photon energies required, THz SFE provides a unique tool to steer chemical reactions [1] or phase transitions [7,8] in the electronic ground state, solely driven by Raman-active lattice vibrations. Shaping of THz pulses [48] to multicolor sequences could enable independent phase and amplitude control of the lattice trajectory along multiple normal coordinates, which is challenging with optical pulses accompanied by parasitic electronic excitations [49].…”
Section: Prl 119 127402 (2017) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
“…Remarkably, due to the low photon energies required, THz SFE provides a unique tool to steer chemical reactions [1] or phase transitions [7,8] in the electronic ground state, solely driven by Raman-active lattice vibrations. Shaping of THz pulses [48] to multicolor sequences could enable independent phase and amplitude control of the lattice trajectory along multiple normal coordinates, which is challenging with optical pulses accompanied by parasitic electronic excitations [49].…”
Section: Prl 119 127402 (2017) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
“…Very recently, we have reported that the degrees of excitation between two different bulk phonon modes of Bi can be controlled by using the optical phase of pump pulses. [40] …”
Section: Coherent Phonons Of Alkali Metal Layers At Metal Surfacesmentioning
confidence: 97%
“…At high fluence, semiconductors may become unstable in the direction of certain phonon coordinates leading to an initially exponential increase of Q qλ , resulting in nonthermal melting. and used to visualize the real-space laser-induced atomic motions from an all-optical experiment [23].…”
Section: A Coherent Phononsmentioning
confidence: 99%